World War Two Simulated: Digital Games and Reconfigurations of the Past by Curtis D. Carbonell (University of Exeter Press, 2023) - Phil Hammond (Eludamos)
A review of Curtis D. Carbonell's monograph World War Two Simulated: Digital Games and Reconfigurations of the Past. Published by University of Exeter Press, 2023. ISBN: 978-1-804-13060-5, 264 pages.